1980
DOI: 10.1111/j.1365-2230.1980.tb01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyositis and malignancy

Abstract: Summary The records of eighteen patients with dermatomyositis were reviewed, of which nine had an associated malignancy. There was no difference in sex distribution, muscle enzyme values, and response to treatment between patients with uncomplicated dermatomyositis and those with co‐existing malignant disease. Cases aged over 40 years with an elevated erythrocyte sedimentation rate and a short interval from onset of dermatomyositis till the patients were referred to hospital may indicate an association with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Of 9 cancer victims among 18 OM patients described by Vesterager et al (19), the mean time from the first consultation for OM to the diagnosis of cancer was only three weeks (1-4 weeks) in five. By cohort analysis, Manchul et al (5) failed to find any increase in the number of subsequent neoplasms in OM-PM patients relative to an age and sex-matched population, although they admitted a markedly high frequency of concurrent malignancy diagnosed within 6 months.…”
Section: Commentmentioning
confidence: 90%
“…Of 9 cancer victims among 18 OM patients described by Vesterager et al (19), the mean time from the first consultation for OM to the diagnosis of cancer was only three weeks (1-4 weeks) in five. By cohort analysis, Manchul et al (5) failed to find any increase in the number of subsequent neoplasms in OM-PM patients relative to an age and sex-matched population, although they admitted a markedly high frequency of concurrent malignancy diagnosed within 6 months.…”
Section: Commentmentioning
confidence: 90%
“…In spite of recent advances in corticosteroid and immunosuppressive therapy, the prognosis is not always favorable. One reason for this poor outcome is the disease's association with internal malignancy; the reported frequency of this complication varies greatly (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Well-controlled statistical studies are needed to determine its relative importance.…”
Section: Introductionmentioning
confidence: 99%
“…The first two cases of DM and malignancy, one of them a breast carcinoma, were described in the second decade of the 20th century (17,21,22). Numerous reports during the following seventy years have shown that DM frequently coexists with a wide spectrum of neoplasticconditions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Nevertheless, the nature of these relationships is not understood (8).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between dermatomyositis (DM) and malignancy is well documented (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In most individuals, treatment of neoplastic disease is followed by a remission ofDM (1,8,11,18,19), but, in some patients, such a beneficial effect is less prominent (6,20).…”
Section: Introductionmentioning
confidence: 99%